Vāmana Malhāra sãsmaraṇa - Somaṇa, Añjalī Aruṇa; Rāṭhī, Sunandā (Śrīmatī Nāthībāī Dāmodara Ṭhākarasī Mānavya āṇi Vāṇijya Mahilā Mahāvidyālaya, 1982)
Souvenir published on the occasion of the birth centenary of Vaman Malhar Joshi, 1882-1943, Marathi litterateur and social activist.